EFEKTIVITAS KESESUAIN WAKTU PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DENGAN HASIL BELAJAR SISWA - Maulida Yunita Rahmah; Siti Shopiyah (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2022)
This research was motivated by time learning at night. The purpose of this study was to determine the learning process of Islamic Religious Education and to determine the learning outcomes of Islamic religious education at SMAQ Al-Ihsan Kebagusan, Pasar Minggu, South Jakarta. The research method used in this study is a qualitative method with a descriptive approach. The location of this research is at SMAQ Al-Ihsan Pasar Minggu, South Jakarta. The primary data sources of this study were obtained from interviews with the principal of SMAQ Al-Ihsan, Islamic religious education teachers and several students of SMAQ Al-Ihsan. The secondary data form of documentation that was taken directly when the authors observed. Data collection techniques in this study were in the form of observation, interviews and documentation. The data analysis technique uses data reduction, data presentation and data verification. The results of the study show that: the effectiveness of learning Islamic religious education at night at SMAQ al-Ihsan Pasar Minggu, South Jakarta is quite effective, it can be seen from several indicators that have been achieved, namely the first indicator in terms of quality. Second, the indicator of the suitability of the level of teaching. Third, incentive indicators, and finally time indicators. Although SMAQ al-Ihsan has reached indicators of learning effectiveness, there are still some things that need to be improved, both in terms of educators and students. The results of the implementation of Islamic religious education learning at night are quite good. This can be seen from the achievement of indicators of student learning outcomes and final grades that are above average Keywords: Learning at Night; Learning Outcomes; Islamic Religious Education